"A Give Grief Kind of Guy": Help‐Seeking, Status, and the Experience of Helpers at a University IT Help Desk. Issue 1 (7th May 2018) - Seeley, J. Lotus
Abstract : Returning the helper to studies of help‐seeking highlights how organizational status is interactionally (re)produced. Using interview and ethnographic data of IT support workers in a medical school, I illuminate how organizational status hierarchies develop independently of organizational rank or authority. Status both structures and is (re)produced through requestors' enactment of deference and/or face‐threatening acts; backstage interpretive processes among helpers naturalize and legitimate status‐based interaction styles. High‐status requestors' failure to protect helpers' face does not flow naturally from organizational status but is the result of active meaning‐making processes with meso‐level implications.